2021
DOI: 10.1038/s41467-020-20717-9
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin-CALCRL axis controls relapse-initiating drug tolerant acute myeloid leukemia cells

Abstract: Drug tolerant/resistant leukemic stem cell (LSC) subpopulations may explain frequent relapses in acute myeloid leukemia (AML), suggesting that these relapse-initiating cells (RICs) persistent after chemotherapy represent bona fide targets to prevent drug resistance and relapse. We uncover that calcitonin receptor-like receptor (CALCRL) is expressed in RICs, and that the overexpression of CALCRL and/or of its ligand adrenomedullin (ADM), and not CGRP, correlates to adverse outcome in AML. CALCRL knockdown impai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 63 publications
0
46
0
Order By: Relevance
“… 27,28 Interestingly, CALCRL has just been proposed as a master regulator of RICs in preclinical models of AML. 29 Although the association of CALCRL with OS and EFS has previously been shown for adult patients with AML, a direct association with the risk of relapse has not been described before, to the best of our knowledge. The clinical association of CALCRL expression with the risk of relapse in the pediatric AML population supports the biological role of CALCRL as a marker of stemness and a master regulator of RICs in human AML.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“… 27,28 Interestingly, CALCRL has just been proposed as a master regulator of RICs in preclinical models of AML. 29 Although the association of CALCRL with OS and EFS has previously been shown for adult patients with AML, a direct association with the risk of relapse has not been described before, to the best of our knowledge. The clinical association of CALCRL expression with the risk of relapse in the pediatric AML population supports the biological role of CALCRL as a marker of stemness and a master regulator of RICs in human AML.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, knockdown of CALCRL in human AML cell lines has been shown to prolong the survival of mice in AML xenotransplantation models and increase the sensitivity toward chemotherapy. 29 Further studies are necessary to determine the therapeutic efficacy of antibody- or small molecule-based inhibition of CALCRL and/or its ligands ADM and calcitonin gene-related peptide alone and in combination with chemotherapy in pediatric and adult AML.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis model established in this study consisted of three inflammatory response-related genes (CALCRL, MMP14, and SELL), which were upregulated in LGG tumor tissues. The CALCRL gene codes the calcitonin receptor-like receptor which is a seven-transmembrane domain G-protein-coupled receptor (Larrue et al, 2021 andAngenendt et al, 2019). Its expression products are closely related to CALCRL and RAMP expressed on the cell surface by co-expression with three receptor active modification proteins (RAMPs).…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, none of the genes belonging to the ADM receptor complex (CALCRL, RAMP2, RAMP3) showed a correlation with endogenous ADM expression. However, it has been recently reported that CALCRL, the receptor of ADM and CGRP, is also overexpressed in LSC and its genomic ablation impaired the clonogenic capacity of AML cell lines (50) and the frequency of chemotherapy-resistant cells able to initiate leukemia relapse in preclinical models (81). In contrast to ADM, CALCRL was highly expressed in NPM1-mutated cases also carrying the FLT3-ITD (50).…”
Section: Discussionmentioning
confidence: 99%